PENYELENGGARAAN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK DI LINGKUNGAN PEMERINTAH KOTA BATAM - Adinata, Muhammad Andri; Putera, Roni Ekha; Kusdarini, Kusdarini (Dialogue : Jurnal Ilmu Administrasi Publik, 2024)
Batam City is the only city in the Riau Islands Province with a good SPBE index out of the 5 regencies and cities in the province. However, in implementing the SPBE policy, problems were encountered, one of which was related to the lack of coordination between SPBE organizers. This creates a discrepancy between the predicate achieved and what is implemented. Bearing in mind that the SPBE maturity level of the Batam City government is the highest in the Riau Islands Province. This research uses a qualitative research method with a descriptive approach. Data collection techniques were carried out by interviews, observation and documentation with the informant selection technique, namely purposive sampling. Meanwhile, the data validity technique uses source triangulation. This research uses the theory of policy implementation proposed by Ripley and Franklin which consists of 2 variables, namely Compliance and What's Happening and Why (What happened and why?) The results of this research indicate that the implementation of the SPBE policy in Batam City has not been implemented optimally. This is caused by (1) minimal understanding of the policy by implementors, unplanned coordination activities between implementers, and no socialization of policy guidelines. (2) factors beyond control that influence the implementation process, namely the agency's lack of awareness of the existence of policy guidelines. (3) inadequate infrastructure factors, and very rapid technological development factors. Thus, the Batam City Communication and Information Department as the main actor needs to fix these problems so that the implementation of the SPBE policy can run effectively